(untitled) (Current Problems in Rail Vehicles, 2021)
The paper summarizes the facts involved in wheelset-track interaction and results from obtained experience within the testing operation of the new DPMB tram branch junction of Vignol’s rail track. The flangeway width was set in relation to the nominal and the limit parameters of all types tram wheelset for optimization of the wheelset-track interaction. Small technical troubles appear during the testing operation and it was necessary to find their reason. Analysis of the actual wheelset-track interaction shows that the mentioned troubles do not constitute any restriction for using of this type turnout structure in DPMB. The troubles absolutely disappear by progressive optimization of common types of trams maintenance and by unification of parameters of historical trams.